المشكلات الأكاديمية التي تواجه طلبة الدراسات العليا في كلية التربية بجامعة دمشق: المشكلات الأكاديمية التي تواجه طلبة الدراسات العليا في كلية التربية بجامعة دمشق (Journal of Hama University, 2025)
The research aimed to identify the academic problems facing post-graduate students at the Faculty of Education at the University of Damascus. The research sample consisted of (58) male and female students. The researcher followed the descriptive approach because it is appropriate for the purposes of the current research, and designed a questionnaire consisting of (40) items as a tool to achieve the research objectives.One of the most important results of the research is the presence of a high rating in the problems faced by postgraduate students in the total grade and its axes, with a rank average of (3.52) for the total grade. There are also no statistically significant differences between the average scores of graduate students at the University of Damascus on the questionnaire due to the variables of gender and specialization. There are statistically significant differences between the average scores of graduate students at the University of Damascus on the questionnaire due to the age variable in favor of those aged (23-30) in the two axes (problems related to research topics - problems related to academic supervision), and the differences in the axis (problems related to student researchers) Came in favor of age (30-35), and there were no differences in the total score.
Keywords: Academic Problems – Post-graduate Students.